PENERAPAN METODE KARYA WISATA MELALUI MEDIA DIGITAL DALAM PEMBELAJARAN MENULIS KREATIF PUISI ISLAMI PADA SISWA KELAS X SMA N 2 BANDAR BARU KABUPATEN PIDIE JAYA - Nurkhalidah Nurkhalidah; Nurlaili Nurlaili; Nuraiza Nuraiza (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2023)
The aims of this study were 1) to describe the improvement in the quality of the process of writing Islamic poetry using the field trip method for class X students of SMA N 2 Bandar Baru, Pidie Jaya Regency: 2) to describe the quality of the results of writing Islamic poetry using the field trip method to class X students of SMA N 2 Bandar Baru Pidie Jaya Regency. This research is in the form of classroom action research. The research subjects used were 25 students of class X SMA N 2 Bandar Baru. The data source used is the implementation of learning to write poetry and the value of poetry writing skills for class X SMA N 2 Bandar Baru. Data collection techniques in the form of observation, interviews, and documentation. While the data collection tools are in the form of test and non-test techniques. The technique used for data analysis is descriptive comparative, namely comparing the percentages between cycles. The research process was carried out in two cycles. Each cycle consists of four stages, namely 1) planning: 2) implementation of action: 3) observation: and 4) reflection. Based on the results of the study it can be concluded that, improving the quality of the learning process of writing poetry on the performance of cycle I teachers can obtain KKM scores in the SMA. The conclusion from this study is that the use of the field trip method can improve the quality of the process and learning outcomes of writing Islamic poetry for class X students of SMA N 2 Bandar Baru, Pidie Jaya Regency, in the 2022/2023 academic year.